Dielectric Properties Of Kenaf-Based Kraft Paper For High Voltage Insulation - Nor Azli, Muhammad Aid'zuddin (Universiti Sains Malaysia, 2018)
Paper is broadly utilized in various engineering applications due to its physical properties and ease of manufacture. Therefore, paper has been designed or chosen as an electrical insulation material for parts in high voltage (HV) technology. However, kenaf is a new material that has been newly introduced to act as an insulating material for high voltage insulation system. Therefore, in order to use kenaf material for electrical purposes, kenaf characteristics need to be studied before can be used in electrical equipment as a part of insulation system. In this research, three type of dielectric test will be conducted on 2 mm kenaf-based Kraft paper (KBKP) to determine its dielectric properties based on British Standard (BS EN 60641-2:2004) pressboard and presspaper for electrical purposes - part 2: methods of tests. This three type of test are moisture content, oil absorption and electric strength in air test. The results showed that the moisture content of this KBKP is 3.15 % while for the oil absorbency is 1.88 %. The electric strength obtained from the electric strength in air test is 12.83 kV/mm. After referred to the British Standard (BS EN 60641-3-1: 1994) pressboard and presspaper for electrical electrical purposes – part 3: specifications for individual materials, this KBKP is possible to act as an insulating material for high voltage insulation system.